2019
DOI: 10.1001/jamaneurol.2019.0905
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intrathecal Immunoglobulin G Synthesis With Disability Worsening in Multiple Sclerosis

Abstract: ; for the German Competence Network of Multiple Sclerosis IMPORTANCE Reliable biomarkers associated with disability worsening in multiple sclerosis (MS) are still needed. OBJECTIVE To determine a possible association of intrathecal IgG synthesis and early disability worsening as measured by Expanded Disability Status Scale (EDSS) scoring in patients with relapsing-remitting MS or clinically isolated syndrome. DESIGN, SETTING, AND PARTICIPANTS Cerebrospinal fluid measurements and clinical data from the observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 35 publications
7
50
0
Order By: Relevance
“…By contrast, OCB positivity failed to predict early disease activity in our study. This finding favoring the prognostic value of quantitative IgG synthesis over OCB was also indicated by several large studies before (10,(36)(37)(38)(39). A recent prospective study with 1,376 German patients found that patients with an elevated IgG index were twice more likely to develop disability worsening 4 years after onset, whereas the presence of OCB failed to show a higher risk of EDSS worsening (10).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…By contrast, OCB positivity failed to predict early disease activity in our study. This finding favoring the prognostic value of quantitative IgG synthesis over OCB was also indicated by several large studies before (10,(36)(37)(38)(39). A recent prospective study with 1,376 German patients found that patients with an elevated IgG index were twice more likely to develop disability worsening 4 years after onset, whereas the presence of OCB failed to show a higher risk of EDSS worsening (10).…”
Section: Discussionmentioning
confidence: 75%
“…Given its low cost and easy accessibility, IgG index is still considered a potential candidate for MS diagnosis despite a relatively low sensitivity (50-75% among MS patients) (3). Studies on its specificity, however, generated mixing results (7)(8)(9)(10). Furthermore, the prognostic value of IgG index or OCB remains undetermined based on existing evidence (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Shift in the balance between Tregs and proinflammatory T-cells [44][45][46][47] Lower percentage of CD4 + Foxp3 Tregs, memory CD4 and CD8 cells and CD56 high NK Cells 44,46,47 Increased Th17 cell responses 48 Low TCR diversity 49…”
Section: Immunological Features In the Bloodmentioning
confidence: 99%
“…Detection of CSF IgM OCB 50,51 Elevated IgG Index 48 Elevated levels of NfL in CSF or serum [52][53][54][55] CSF CXCL13 56,57 1000 patients with clinically isolated syndromes (CIS) characteristic of MS showed that a high brain T2 lesion load at baseline was the most robust predictive factor for future disability accrual. 68 Tintore et al 13 used a Barcelona-based inception cohort and, like Malpas et al, 14 defined aggressive MS as reaching an EDSS ⩾6.0 within 10 years of disease onset.…”
Section: E Biomarker Correlatesmentioning
confidence: 99%
“…B cells play an important role in the pathophysiology of multiple sclerosis (MS). B cells are detected in MS lesions and cerebrospinal fluid (CSF), and the persistence of intrathecal oligoclonal immunoglobulin G (IgG) bands is a fundamental hallmark of disease and associated with worsening disability [5,16]. Phase 3 clinical trials have demonstrated that B cell-depleting therapies are effective in reducing clinical and MRI activity in relapsing and progressive forms of disease [9,10,24].…”
Section: Introductionmentioning
confidence: 99%